Kesan perceraian ke atas kanak-kanak: perspektif pekerja sosial - Nuraimirah Zainun,; Norulhuda Sarnon @ Kusenin,; Nur Saadah Mohamad Aun, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Statistic shows that many divorce cases occur within the first five years of marriage that involved both spouses and children. These give a negative impact on the collapse of the family institution in Malaysia. Hence, this study is conducted to examine the psychosocial effects among children in divorced families. This study used qualitative approach and phenomenological design which involved ten social workers as informants. The results were obtained from the social workers’ perspective only by using purposive sampling. Data of this study were analyzed using thematic analysis and Atlas.ti version 8 computer software. Results showed that there are three main effects which are (i) psychological; (ii) change in behavior and (iii) lack of financial resources. Changes from core family structure to singleparent family have led to these changes. These findings are expected to contribute for a better intervention among social workers to ensure the well-being of children and families in the future.